Reinforcement of perceptual inference: reward and punishment alter conscious visual perception during binocular rivalry - Wilbertz, Gregor; van Slooten, Joanne; Sterzer, Philipp (Frontiers in Psychology, 2014)
Perception is an inferential process, which becomes immediately evident when sensory information is conflicting or ambiguous and thus allows for more than one perceptual interpretation. Thinking the idea of perception as inference through to the end results in a blurring of boundaries between perception and action selection, as perceptual inference implies the construction of a percept as an active process. Here we therefore wondered whether perception shares a key characteristic of action selection, namely that it is shaped by reinforcement learning. In two behavioral experiments, we used binocular rivalry to examine whether perceptual inference can be influenced by the association of perceptual outcomes with reward or punishment, respectively, in analogy to instrumental conditioning. Binocular rivalry was evoked by two orthogonal grating stimuli presented to the two eyes, resulting in perceptual alternations between the two gratings. Perception was tracked indirectly and objectively through a target detection task, which allowed us to preclude potential reporting biases. Monetary rewards or punishments were given repeatedly during perception of only one of the two rivalling stimuli. We found an increase in dominance durations for the percept associated with reward, relative to the non-rewarded percept. In contrast, punishment led to an increase of the non-punished compared to a relative decrease of the punished percept. Our results show that perception shares key characteristics with action selection, in that it is influenced by reward and punishment in opposite directions, thus narrowing the gap between the conceptually separated domains of perception and action selection. We conclude that perceptual inference is an adaptive process that is shaped by its consequences.